Planeación didáctica para la atención a personas con discapacidad en contextos de servicios educativos. Manual de estrategias curriculares didácticas en la Fundación Construyamos un Sueño de la ciudad de Latacunga. - Almachi Guisha, Johanna (2016)
This research is about a manual teaching curriculum strategies in the Foundation's Build a Dream, is made from the problems evidenced by the lack of attention to people with disabilities. This is why it is considered essential and important to analyze the object of study curriculum design as a methodology and action as a process of elaboration and the result which are reflected constitutes, as this will develop their different capabilities and educational opportunities social, cultural and political. As technical project disabilities, my goal is to improve care for people with disabilities by developing a handbook of educational curriculum strategies, where the variables are: educational planning and care for people with disabilities, for research have been used different methods such as analytical, deductive, historical, dialectical, empirical, statistical and descriptive, that by applying the same was possible to obtain results that helped the researcher with a solution to the lack of care for people with disabilities, concluding that it is necessary to indicate that the use of educational curriculum strategies is of great importance and usefulness for work, and therefore attention to the teaching of people with disabilities. The implementation of a curriculum manual teaching strategies for people with disabilities, is a proposal based on equity, equality and especially the inclusion and attention, offering the opportunity to potentiate learning by developing their skills.